Термін як естетична сокира, або ще раз про неоромантизм Лесі Українки - Моклиця, Марія; Moklytsia, Maria (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті йдеться про неоромантизм у творчості Лесі Українки як стереотип та ідеологему, яка змінює в суспільній свідомості роль письменниці в україн- ській культурі з визначного драматурга на поетесу. Важливо відокремити новаторство Лесі Українки в царині поезії (переважно неоромантичного плану), прози (переважно неореалістичної) і драматургії (насамперед неокласицист- ської). Закриту класицистську форму Леся Українка перетворила на відкриту неокласицистську й завдяки цьому змогла сягнути в драматургії рівня першо- рядних новаторів ХХ ст. The article deals neoromanticism in Lesіa Ukrainka as ideologeme and stereotype that changes in the public mind the role of the writer in Ukrainian culture: from prominent playwright on poet. Compliance tradition and innovation − one of the most important aspects of the study of the Lesіa Ukrainka, but here there are many layers of previous decades when ideologeme markers marked all the main approaches. It is important to separate the Lesіa Ukrainka innovation in the field of poetry (mostly neoromantic plan), prose (usually neorealistic) and drama (especially neoclassicistic). The paradox of innovation in the field of drama lies primarily in the modernization of the classicism, which at the time of Lesіa Ukrainka was perceived as anti-romantic and anti-modernist, therefore outdated tradition, especially in terms of form. Lesіa Ukrainka turned closed classicistic form into open neoclassicistic or modernist, and thus was able to reach in the drama of the primary innovators of the twentieth century.
Term as Aesthetic ax, or Again on Neoromanticism of Lesіa Ukrainka
Keywords: Леся Українка; неоромантизм; неореалізм; неокласицизм; модернізм; драматургія; Lesia Ukrainka; neoromanticism; neorealism; neoclassicism; modernism; drama